Analisis Sistem Antrian Dalam Upaya Optimalisasi Pelayanan Pada PT. Bank Rakyat Indonesia (Persero) Tbk. Kantor Unit Pasar Kota Rangkasbitung - Jauhar Latifah; Eri Nuryanah; Indra Laksana Noerwan; Andri Susilo (E-Journal Studia Manajemen, 2014)
Queuing problem is a part that cannot be avoided in the banking system. In banking, serving customers speed can improve customer satisfaction. The aim of this study was to determine the queuing system is applied to PT. Bank Rakyat Indonesia (Persero) Tbk. Rangkasbitung. In this study, the authors use the case study method. Data used to conduct research is secondary data and primary data. Data collection techniques used to obtain the necessary data is by observation and interview. Based on the research results, Discipline imposed queue is First Come First Serve (FCFS) or FIFO, from teller utilization BRI Rangkasbitung reaches 0.90 or 90% and the average customer in the queue the longest occurred in the 10:00 to 11:00 time period where the average customer waiting in line at the period of time as much as 7.62454 (8 customer), the average customer waiting in the system as much as 9.47454 (9 customer). The average time spent by a person of customers to wait in the queue is 0.21179 hours, the longest time spent in the system is a long .20869 hours. In order for teller service can run optimally so that it can overcome the problem of the queue should the bank provide additional teller opened number one for transaction deposits, withdrawals, and other services.